Political Myths in Armenian Pre-Election Television Debates - Martirosyan, Liana (Bulletin of Yerevan University B: Philology, 2023)
The mythologizing of political life has always occupied the creative mind of man. For years, researchers have pondered over the formulation of political myths and their functions. Even today, they are considered an integral part of the arsenal of every political force and are used for the creation and construction of a new reality. Their use becomes important during the socio-cultural crises of society, when a person has a problem of orientation and choice. The task of the work is to identify manipulative technologies and tools that are used to achieve power during televised debates․ The methodological basis of the article is made up of analysis methods, comparisons, and generalizations. From the conducted research, it became clear that the forces that biased the 2018 elections mainly tried to build the traditional myths about the conspiracy, hero-savior, golden age, and revolutions. They were built using a number of manipulation technologies.